Evaluating the Indigenous Probiotic Lactococcus lactis D4 as an Adjuvant to Capecitabine: Modulation of NF-κB in a Colorectal Carcinogenesis Model - Arli Suryawinata; M Iqbal Rivai; Rini Suswita; Irwan; Avit Suchitra; Raflis Rustam (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Chronic inflammation driven by the nuclear factor kappa-B (NF-κB) signaling pathway is a fundamental driver of colorectal cancer (CRC) pathogenesis, promoting tumor survival, mucosal proliferation, and profound chemoresistance. Capecitabine is a standard first-line fluoropyrimidine chemotherapy; however, its clinical utility is frequently compromised by dose-limiting toxicities and the activation of inflammatory feedback loops. Lactococcus lactis D4, a novel probiotic strain isolated from traditional Indonesian fermented buffalo milk (dadih), possesses well-documented immunomodulatory properties. Methods: A randomized controlled experimental study was conducted utilizing male Sprague-Dawley rats (n=37). Colorectal carcinogenesis was chemically induced via intraperitoneal administration of 1,2-dimethylhydrazine (DMH). Following strict histopathological confirmation of malignancy, the cohort was randomized into five distinct groups: Negative Control, Positive Control, L. lactis D4 monotherapy, Capecitabine monotherapy, and Combination therapy. Interventions were administered daily for 14 days. Outcomes included NF-κB protein expression assessed via immunohistochemistry (IHC) and targeted gene expression quantification via RT-qPCR. Results: Immunohistochemical analysis demonstrated that the positive control group exhibited significantly elevated NF-κB protein expression (35.87 ± 13.53%). Capecitabine monotherapy significantly reduced this expression to 16.07 ± 3.79% (p=0.003). The Combination therapy achieved a profound reduction in NF-κB protein expression down to 12.99 ± 4.92%; however, this was not statistically superior to Capecitabine alone (p=1.000). Conversely, RT-qPCR analysis revealed no statistically significant difference in NF-κB mRNA levels among the experimental groups (p=0.094). Conclusion: The combination of L. lactis D4 and Capecitabine effectively reduces NF-κB protein expression in a preclinical CRC model, achieving suppression levels comparable to primary chemotherapy. The distinct discordance between the significant protein suppression and the sustained mRNA expression levels suggests potential post-transcriptional or post-translational regulatory mechanisms that warrant further targeted molecular investigation.